Coexistence of splenic marginal zone lymphoma with hepatocellular carcinoma: a case report - Zheng Jian-Ming; Xu Ai-Min; Zhang Shu-Hui; He Miao-Xia (BMC, 2007)
Abstract Background Coexistence of splenic marginal zone lymphoma with hepatocellular carcinoma is rare. Although some reports have suggested the possible pathogenic role of HBV, HCV, chronic and persistent antigenic stimulation in lymphoma, their role in causing lymphomas is still unclear. Case presentation We describe a hepatocellular carcinoma with concomitant splenic marginal zone lymphoma in a 64-year-old Chinese man with cirrhosis. Serum hepatitis B virus surface antigen was positive and antihepatitis C virus antibody was negative. The resected liver mass measuring 4 × 3 × 3 cm was grey and soft with a small area of bleeding, necrosis and intact capsule. Cut surface of the spleen was red-purple and had a diffuse reticulonodular appearance indicative of prominent white pulp. On histologic sections, the liver mass was well and moderately differentiated hepatocellular carcinoma, and the splenic tumor was a specific low-grade small B-cell lymphoma. Immunohistochemical staining and gene rearrangement studies supported that the splenic tumor represents a clonal B-cell lymphoma. Therefore, the diagnosis of SMZL was made from the splenic specimen. Conclusion To our knowledge, this is the second case report describing coexistence of hepatocellular carcinoma and splenic marginal zone lymphoma in the course of chronic HBV infection. However, we cannot assert at present that hepatitis B virus is directly involved in splenic lymphomagenesis until more information is collected from more cases in the future.